Framework of an integrated knowledge-based system for functional design automation of mechanical products - Zhang, Wen Yu (2008)
The objective of this research is to develop an integrated knowledge-based functional design framework to support functional design automation by embedding functional reasoning and integrated knowledge-based approaches.